Characterization of patients with venous ulcer assisted in a public hospital stomatherapy clinic (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To evaluate the profile of patients with venous ulcer in ambulatory care. Method: Retrospective study performed in a stomatherapy clinic of a general hospital. Data were obtained from the care records of the period between October 2014 and March 2015. Results: It was observed a predominance of women (68.2%), age group over 60 years (51.2%) and domicile in Fortaleza/CE (63.4%). Single ulcers (58.5%) and unilateral ulcers (75.6%) were the most frequent. The principal comorbidities found were systemic arterial hypertension (39%) and diabetes mellitus (30%). The treatment was clinical in 82.9% of the cases, with a higher adhesion to compressive therapy (60.9%) and with the use of dressings containing essential fatty acids (38.7%) and hydrogel (32.2%). Regardi the outcome, the continuity of outpatient treatment predominated (56%). Conclusion: The results of the study are considerable and it is important others searches in the area, besides helping to plan nursing care for these patients.